Preservation of the Historic City of Bandung through the Building of Cultural Heritage Group A - Maksey Muhammad (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2020)
Bandung is one of the historical cities in Indonesia. Therefore, there are many historic heritage buildings adorning the city. According to local regulations, there are at least around 1700 cultural heritage buildings in the city of Bandung. The effort to preserve historic buildings has been carried out by the Bandung city government to maintain the historical value that exists in each building and its area. Along with the changing times, changes or shifts in the environment often occur in historic areas including social, cultural and economic. This has an effect on the complexity of preserving historic buildings, especially those included in class A cultural heritage buildings. One area that has a high historical value is Jalan Braga. Along the Braga street there are many classes A cultural heritage buildings, one of which is the Insulinde Building. The Insulinde building was built in 1917 as an oil factory office. During its establishment, the Insulinde building has changed functions 6 times. Its location in the Braga area makes adjustments to the building to the area need to be considered to see changes in the environment that occurs from year to year. This research uses qualitative methods by collecting data through literature studies and field observations. From the implementation of this research, it is expected to be able to contribute to the preservation of historic areas through its buildings as well as the adjustment of building functions seen from the shifting environment of the region.